Synthesis and Biological Evaluation of Thieno[2,3-c]pyridines and Related Heterocyclic Systems - HASSAN, A.Y.; MOHAMED, H.A. (Asian Journal of Chemistry, 2010)
Reaction of 3,5-bis(pyrrolidene)-4-piperidone (1), with malononitrile. Ethyl cyanoacetate and benzoyl acetonitrile in basic medium to give pyrano[3,2-c]pyridine derivatives (2a-c). The treatment of compounds 2a-c with acetic acid and ammonium acetate led to the conversion of pyran ring to pyridine ring in compound 3a-c. Reaction of 1 with 2 mole of malononitrile afforded aminoquinolizinone derivative (4a). Reaction of 5 with thiosemicarbazide, acetylacetone and cyanothioacetamide gave pyrazolo[3,4-c]pyridine (6), pyrido[4,3-c]-4-cyclohexene 5-one and pyrido[2,3-c]pyridine-2-thione (8) derivatives. Interaction of 8 with p-cyanoacetophenol afforded thieno[2,3-b]-(1,6)naphthyridine derivative (10). The formation of thieno[2,3-c]pyridine (11a-c) from Gewald reaction products. On the other hand, reaction of 11a,b with carbon disulfide gave pyridothienopyrimidine derivatives (12a,b). Alkylation of 12a,b with ethyl iodide gave 13b and 14a. Condensation of 1-methyl-4-piperidone with malononitrile gave 1-methyl-4-piperidonylidene malononitrile (15). Reaction of 15 with p-chlorobenzaldehyde afforded 3-p-chlorobenzylidene-1-methyl-4-piperidonylidene malononitrile (16). 6-Amino-5,7,7-tricyano-8-p-chloro-phenyl-2- methyl-1,2,3,4,7,8-hexahydroisoquinoline (17) was performed by the treatment of 1-methyl-4-piperidone with a mixture of one equivalent of p-chlorobenzaldehyde and two equivalent of malono-nitrile. The synthesized compounds were screened for their in vitro antitumor activity at the National Center Institute (NCI).